2022
DOI: 10.3389/fimmu.2022.847171
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus Multiplexes Death-Effector Deoxyribonucleosides to Neutralize Phagocytes

Abstract: Adenosine synthase A (AdsA) is a key virulence factor of Staphylococcus aureus, a dangerous microbe that causes fatal diseases in humans. Together with staphylococcal nuclease, AdsA generates deoxyadenosine (dAdo) from neutrophil extracellular DNA traps thereby igniting caspase-3-dependent cell death in host immune cells that aim at penetrating infectious foci. Powered by a multi-technological approach, we here illustrate that the enzymatic activity of AdsA in abscess-mimicking microenvironments is not restric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(53 citation statements)
references
References 68 publications
(120 reference statements)
3
50
0
Order By: Relevance
“…More precisely, we incubated wild-type S. aureus Newman or its adsA variant in the presence or absence purine deoxyribonucleoside monophosphates (dAMP or dGMP) to obtain conditioned culture media, which were filter-sterilized and added to vehicle-or (R)-DI-87-exposed human U937 macrophages. In line with earlier studies (Thammavongsa et al, 2013;Winstel et al, 2018;Winstel et al, 2019;Tantawy et al, 2022), macrophage killing required purine deoxyribonucleoside monophosphate-conditioned media and adsAproficient staphylococci as only wild-type S. aureus Newman and dAMP-or dGMP-supplemented media triggered phagocyte cell death in this approach (Figure 2K-L). However, (R)-DI-87-exposed cells could not be killed in these experiments supporting the idea that pharmacological inhibition of host dCK can shield macrophages from S. aureus-and AdsA-driven cell death (Figure 2K-L).…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…More precisely, we incubated wild-type S. aureus Newman or its adsA variant in the presence or absence purine deoxyribonucleoside monophosphates (dAMP or dGMP) to obtain conditioned culture media, which were filter-sterilized and added to vehicle-or (R)-DI-87-exposed human U937 macrophages. In line with earlier studies (Thammavongsa et al, 2013;Winstel et al, 2018;Winstel et al, 2019;Tantawy et al, 2022), macrophage killing required purine deoxyribonucleoside monophosphate-conditioned media and adsAproficient staphylococci as only wild-type S. aureus Newman and dAMP-or dGMP-supplemented media triggered phagocyte cell death in this approach (Figure 2K-L). However, (R)-DI-87-exposed cells could not be killed in these experiments supporting the idea that pharmacological inhibition of host dCK can shield macrophages from S. aureus-and AdsA-driven cell death (Figure 2K-L).…”
Section: Resultssupporting
confidence: 90%
“…Of note, (R)-DI-87-mediated inhibition of mammalian dCK in U937 or U937 MФ efficiently prevented dAdo-or dGuo-induced cell death in a dose-dependent manner (Figure 2A-D; supplementary Figure 1A-D). Moreover, these effects resembled the phenotype of dCK-deficient U937 or U937 MФ, which were found to be refractory to dAdo-or dGuo-mediated cytotoxicity (Figure 2A-D) (Winstel et al, 2018;Tantawy et al, 2022). In addition, we observed that pre-treatment of primary human CD14 + monocytes or human monocyte-derived macrophages (HMDMs) with (R)-DI-87 blocked dAdo-or dGuotriggered cytotoxicity suggesting that dCK inhibition may suppress the toxigenic properties of staphylococcal death-effector deoxyribonucleosides (Figure 2E-H).…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…The Gram positive bacterium Staphylococcus aureus exploits adenosine accumulation through several mechanisms. S. aureus expresses a surface protein adenosine synthase A (AdsA) that generates adenosine from ATP, ADP and deoxyadenosine, as well as the cytotoxic deoxyguanosine ( Winstel et al., 2018 ; Tantawy et al., 2022 ). In a model of renal abscess and septicemia, the resulting NETosis provides S. aureus with a source of DNA and nucleosides for adenosine synthesis.…”
Section: Adenosine Mediates Pro and Anti-inflammatory Cascadesmentioning
confidence: 99%